The Interval Between Matches Significantly Influences Injury Risk in Field Hockey - Mason, Joel; Rahlf, Anna Lina; Groll, Andreas; Wellmann, Kai; Junge, Astrid; Zech, Astrid (International Journal of Sports Medicine, 2021)
Fixture congestion increases injury risk in football, but how it impacts other sports is unclear. The aim of this study was to identify associations between match density and injury incidence in field hockey players. Injury data from a prospective cohort study of professional and youth players was analysed in two ways. Inter-match intervals were clustered into<2424-hours, 3–7-days, and 13 + days, and injury rate ratios (IRR) were calculated to identify differences between clusters in match injuries. Separately, a Lasso-penalised Poisson regression model was used to determine the association between match load across the previous 24-hours, 3-days, 7-days and 14-days, and match and training injuries. Injury rates in matches within 24-hours of the previous match were mostly significantly higher when compared to matches after 3–7-days (IRRs: 3.78; 6.77, P = 0.003; 0.005). While a higher match exposure in the preceding 24-hour and 3-day periods was associated with higher combined match and training injury rates (β̂ = 0.0001; 0.0018), a higher match exposure in the previous 7-and 14-day periods was associated with a reduced injury rate (β̂ = –0.0001; –0.0005). Due to the increased injury risk in matches 3-days and especially 24-hours following the previous fixture, match distribution should be cautiously planned.
Keywords: match density; fixture congestion; injury; team sport; schedule